Path-Dependent Development of Mass Housing in Moscow, Russia. - Gunko, Maria; Bogacheva, Polina; Medvedev, Andrey; Kashnitsky, Ilya (Springer Open, 2018)
Since the 1950s, Moscow s housing development has been underlined by modernist planning schemes. From the 20th to 21st centuries, the quality and appearance of apartment buildings changed, but housing estates designed as coherent neighbourhoods not only remain the principal type of housing organization but are still being constructed in Moscow and its suburbs. Though the concept itself has not been challenged by policy-makers and planners, by the end of the 20th century it became apparent that early housing estates have become a problem due to poor quality of construction. In 2017, the Moscow Government announced a highly controversial program suggesting the demolition of housing estates built between the 1950s and 1960s. Our contribution analyzes the history of housing estates development in Moscow aiming to understand what has led to the adoption of the 2017 renovation program. If this program ends up being fully implemented, along with planned renovation of former industrial areas, the cityscape of Russia s capital will be completely redefined.
Keywords: Wohnungswesen; Wohnsiedlung; Wohnungsbau; Großwohnsiedlung; Fallbeispiel